Ultrastructural analysis of uninstrumented root canal areas following various irrigation regimens - Barac Radomir; Popović Jelena; Živković Slavoljub; Mitić Aleksandar; Nikolić Marija; Gašić Jovanka (Stomatološki glasnik Srbije, 2016)
Introduction During endodontic treatment smaller or larger areas of root canal wall remain non-instrumented. This can affect prognosis of endodontic treatment as some bacteria may be left behind. The purpose of this study was to evaluate the morphology of non-instrumented areas of the root canal wall using scanning-electron-microscopy (SEM) after completed instrumentation and various irrigation regiments. Materials and Methods Eighteen single-rooted extracted teeth were divided into the six groups. One tooth in each group represented a control sample. In all samples only one half of the canal was instrumented using ISO 40 hand files. Control samples were subjected to an irrigation protocols without instrumentation. Irrigants used were physiological saline, 3% sodium hypochlorite and 15% of ethylene-diamine-tetra-acetate. Irrigation protocol included using each of these irrigants alone, or a combination of NaOCl and EDTA, as well as their combination with final irrigation using NaOCl or chlorhexidine. Then after, roots were sectioned longitudinally and prepared for SEM. Results Saline irrigation left pulpal debris on uninstrumented areas of the canal wall. Irrigation with 3% NaOCl left behind canal wall with different forms of calcospherites. However, after EDTA irrigation dentin appeared as an undulating surface with open tubules without a smear layer. The combination of NaOCl and EDTA showed remnants of calcospherites and open slightly widened dentinal tubules. Final irrigation with NaOCl on the uninstrumented areas showed enlarged dentinal tubules along with dentinal erosion, while after final irrigation with CHX clean dentin and open dentinal tubules without smear layer were noted. Conclusion From the morphological point of view, the most favorable effect of irrigation on both uninstrumented and uninstrumented canal walls was achieved after irrigation with NaOCl and EDTA or NaOCl, EDTA and chlorhexidine as the final irrigant.